Overexpression of Circular RNA ciRS‐7 Abrogates the Tumor Suppressive Effect of miR‐7 on Gastric Cancer via PTEN/PI3K/AKT Signaling Pathway. Issue 1 (7th July 2017) - Pan, Haiyan; Li, Tao; Jiang, Yugang; Pan, Congcong; Ding, Yuanlin; Huang, Zhigang; Yu, Haibing; Kong, Danli
ABSTRACT: Gastric cancer (GC) has one of the highest mortality rates of malignancies globally. Currently, ciRS‐7, a novel circular RNA, has emerged as a potential sponge for miR‐7. However, few studies on ciRS‐7 in GC have been performed. In this study, we investigated the clinical significance and function of ciRS‐7 in GC. First, the expression levels of ciRS‐7 in 102 primary GC tissues and the matched para‐carcinoma tissues were evaluated and the clinical relevance was confirmed in an independent validation cohort (n = 154). Second, the effects of ciRS‐7 on miR‐7, PTEN, and PI3K were evaluated. Finally, the function of ciRS‐7 in GC was analyzed with cell lines and nude mice. The expression of ciRS‐7 was significantly upregulated in GC tissues compared with the matched para‐carcinoma tissues ( P  = 0.0023), and the upregulation of ciRS‐7 was linked to poor survival in the testing ( P  = 0.0143) and validation cohort ( P  = 0.0061). Multivariate survival analysis revealed that ciRS‐7 was probably an independent risk factor of overall survival ( P  < 0.05). Furthermore, overexpression of ciRS‐7 blocked the miR‐7‐induced tumor suppression in MGC‐803 and HGC‐27 cells and led to a more aggressive oncogenic phenotype, via antagonizing miR‐7‐mediated PTEN/PI3K/AKT pathway. ciRS‐7 may act as a prospective prognostic biological marker and a promising therapeutic target for GC. J. Cell. Biochem. 119: 440–446, 2018. © 2017 Wiley Periodicals, Inc. Abstract : ciRS‐7 may act as a prospective prognostic biological marker and a promising therapeutic target for GC patients.